DESKRIPSI KEMAMPUAN ANALISIS MAHASISWA MENYELESAIKAN SOAL GEOMETRI EUCLID BERDASARKAN TEORI VAN HIELE - Abi, Alfonsa Maria; Snae, Louisa M. Y.; Babys, Urni (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
Analytical ability is the competence of connecting information that is broken down into whole parts in determining solutions. Good geometry teaching must be in accordance with the individual's thinking stages. The purpose of this study is to produce a study on the description of students' analytical abilities in solving Euclid's geometry problems based on Van Hiele's theory. The subjects in this study were 20 students of the Mathematics Education study program at the Soe Institute of Education who accessed the Euclid geometry course. The data collection technique used was an interview with 6 (six) students. The data analysis technique follows the Miles and Huberman model. Data validity testing is carried out by triangulating sources. The results of this study indicate that (1) at the introduction stage, students already understand the shape of the geometric shapes; (2) at the analysis stage, students are able to identify the properties of the geometric shapes; (3) at the sequencing stage, students are able to compile a definition of a geometric figure based on the properties between figures and provide an explanation of the relationships between figures; (4) at the deduction stage, students are able to use conjectures from geometric figures correctly and (5) at the accuracy stage, students are able to solve problems with solutions in terms of using conjectures or theorems correctly and are able to provide conclusions. There are also students who do not reach all five stages of thinking completely due to their low understanding of geometry